Proceedings of the Web Conference 2021 2021
DOI: 10.1145/3442381.3450137
|View full text |Cite
|
Sign up to set email alerts
|

“Short is the Road that Leads from Fear to Hate”: Fear Speech in Indian WhatsApp Groups

Abstract: WhatsApp is the most popular messaging app in the world. Due to its popularity, WhatsApp has become a powerful and cheap tool for political campaigning being widely used during the 2019 Indian general election, where it was used to connect to the voters on a large scale. Along with the campaigning, there have been reports that WhatsApp has also become a breeding ground for harmful speech against various protected groups and religious minorities. Many such messages attempt to instil fear among the population ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
32
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 32 publications
2
32
0
1
Order By: Relevance
“…Disinformation is a global phenomenon, taking on different forms and patterns in different parts of the world. Prior work has studied comparative cases of misinformation in places such as Brazil and India, for instance highlighting actors' choice of different platforms according to regional popularity [50], [95], [29], [30], and distinct regional patterns of biased or toxic speech behavior [37], [38], [84]. Some works develop and demonstrate cross-cultural datasets [79] and tools [66].…”
Section: Related Workmentioning
confidence: 99%
“…Disinformation is a global phenomenon, taking on different forms and patterns in different parts of the world. Prior work has studied comparative cases of misinformation in places such as Brazil and India, for instance highlighting actors' choice of different platforms according to regional popularity [50], [95], [29], [30], and distinct regional patterns of biased or toxic speech behavior [37], [38], [84]. Some works develop and demonstrate cross-cultural datasets [79] and tools [66].…”
Section: Related Workmentioning
confidence: 99%
“…Social media response to the ongoing pandemic has received significant research attention: (1) health misinformation [24,25,26], (2) polarization [27,28], (3) disease modeling [29], etc. Counterhate measures along the line of counterspeech research [30,31,32,33] to combat Anti-Asian hate [34], and community blame [35] While the political volatility between India and Pakistan has been extensively studied by social scientists [36,37,38], barring few recent lines of work [5,23,9], social media interactions between the civilians of India and Pakistan has received little or no attention. All recent work on Indian and Pakistani social media [5,23,9] focused on a solitary incident -the 2019 India-Pakistan conflict triggered by the Pulwama terror attack across different social media platforms.…”
Section: Related Workmentioning
confidence: 99%
“…In India, most people identify themselves with a religion, leading to two main groups: Hindus and Muslims, who form 79% and 13% of Indians, respectively [34]. However, the same identifying attribute, religion, is often misused to provoke these groups against each other [33].…”
Section: Introductionmentioning
confidence: 99%
“…either make the readers angry (at a religious group) or urge them to take any action (against that religious group). Saha et al [34] curate a dataset of WhatsApp posts that instill fear of Indian Muslims in the mind of readers. Our investigation found that such fearful posts also contain provoking sentences against the same religious group.…”
Section: Introductionmentioning
confidence: 99%